2004
DOI: 10.1002/app.20179
|View full text |Cite
|
Sign up to set email alerts
|

Alkali–methanol–anthraquinone pulping of Miscanthus x giganteus for thermoplastic composite reinforcement

Abstract: ABSTRACT:The potential of pulp fiber-reinforced thermoplastics is currently not fully explored in composites. One of the main reasons is that pulp fibers are extracted for the use in papermaking and are thus not optimized for use as reinforcements in thermoplastics. Furthermore, currently used processing methods constitute several severe thermomechanical steps inducing premature degradation of the fibers. A systematic development of these composite materials requires the study of both these aspects. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…These values are similar to the modulus of 10 GPa measured on stem fragments by nano-indentation by Bourmaud and Pimbert (2008). Of course, the moduli are much lower than the tensile modulus value of 55 GPa reported by Lundquist et al (2003) for individual fibres extracted from miscanthus stems by a pulping process and mostly composed of cellulose originating from cell walls. Besides, these values are close to tensile moduli of other stem fragments as bamboo, 11−36 GPa (Bourmaud et al, 2018;Gurunathan et al, 2015).…”
Section: Elastic Modulus Of Miscanthus Stem Fragments: Effect Of Genosupporting
confidence: 84%
“…These values are similar to the modulus of 10 GPa measured on stem fragments by nano-indentation by Bourmaud and Pimbert (2008). Of course, the moduli are much lower than the tensile modulus value of 55 GPa reported by Lundquist et al (2003) for individual fibres extracted from miscanthus stems by a pulping process and mostly composed of cellulose originating from cell walls. Besides, these values are close to tensile moduli of other stem fragments as bamboo, 11−36 GPa (Bourmaud et al, 2018;Gurunathan et al, 2015).…”
Section: Elastic Modulus Of Miscanthus Stem Fragments: Effect Of Genosupporting
confidence: 84%
“…To our knowledge, only Georgopulos et al [27] employed autohydrolysed samples of wood and brewery spent grains for reinforcing polypropylene-based composites, and Okuba et al [28] used steamexploded bamboo for improving the properties of PLA-based composites. Other reinforcers have been derived from LCM by physicochemical treatments, including thermomechanical pulping and acid hydrolysis [10], pulping with alkali-methanol-anthraquinone solutions [29], extraction with alkaline solutions [30,31], esterification [8] and carboxymethylation [26].…”
Section: 2) Manufacture Of Biodegradable Composites Made Up Of Pla mentioning
confidence: 99%
“…Composites reinforced with miscanthus stems are being increasingly studied due to attractive mechanical properties associated with their light‐weight compared to glass fibers (Girones et al 2016). The first such study was conducted on Miscanthus × giganteus and centered on the preparation of composites by incorporating fibers that were pulped by the alkaline–methanol–anthraquinone process (Lundquist et al, 2004). Johnson et al (2005) directly included stem fragments of Miscanthus × giganteus into a starch‐based polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies related the initial miscanthus stem properties with the biochemical characteristics of the plant. Lundquist et al (2004) used the smallest units and highest quality cellulose fibers from Miscanthus × giganteus stems thanks to an alkali–methanol–anthraquinone pulping process (Lundquist et al, 2004). They showed that cellulose fibers were thermally stable up to 255°C and had an aspect ratio of 40, a tensile strength of 890 MPa and a Young's modulus of 60 GPa.…”
Section: Introductionmentioning
confidence: 99%